Negative Capacitance for Electrostatic Supercapacitors. Issue 40 (17th September 2019) - Hoffmann, Michael; Fengler, Franz Paul Gustav; Max, Benjamin; Schroeder, Uwe; Slesazeck, Stefan; Mikolajick, Thomas
Abstract: The increasing demand for efficient storage of electrical energy is one of the main challenges in the transformation toward a carbon neutral society. While electrostatic capacitors can achieve much higher power densities compared to other storage technologies like batteries, their energy densities are comparatively low. Here, it is proposed and demonstrated that negative capacitance, which is present in ferroelectric materials, can be used to improve the energy storage of capacitors beyond fundamental limits. While negative capacitance was previously mainly considered for low power electronics, it is shown that ferroelectric/dielectric capacitors using negative capacitance are promising for energy storage applications. Compared to earlier results using (anti)ferroelectric materials for electrostatic energy storage, much higher efficiencies of more than 95% even for ultrahigh energy densities beyond 100 J cm −3 are demonstrated using nonepitaxial thin films suitable for integration on 3D substrates. Stable operation up to 150 °C and 10 8 charging/discharging cycles is further demonstrated. Abstract : Materials with a negative capacitance can improve the energy storage in electrostatic supercapacitors beyond conventional limits. By combining a ferroelectric with a dielectric material in a double layer stack, the negative capacitance effect can be used to achieve ultrahigh energy densities and high storage efficiency. Reliable operation is demonstrated using polycrystalline ferroelectrics together with amorphous dielectrics.